2015
DOI: 10.1586/17512433.2015.1058154
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting muscarinic antagonists

Abstract: Chronic obstructive pulmonary disease (COPD) is a major cause of death and disability worldwide. Inhaled bronchodilators are the mainstay of COPD pharmacological treatment. Long-acting muscarinic antagonists (LAMAs) are a major class of inhaled bronchodilators. Some LAMA/device systems with different characteristics and dosing schedules are currently approved for maintenance therapy of COPD and a range of other products are being developed. They improve lung function and patient-reported outcomes and reduce ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 146 publications
3
43
0
2
Order By: Relevance
“…Tiotropium was associated with higher cardiovascular mortality risk. However, in another context, tiotropium was shown to be more effective in reducing exacerbations than salmeterol and indacaterol, regardless of association with inhaled corticosteroids [27,28]. Moreover, the UPLIFT study (Understanding Potential Long-term Impacts on Function with Tiotropium), a double-blind, randomised, placebo-controlled clinical trial conducted on >6000 patients (followed up for 4 years), revealed a reduced acute myocardial infarction and cardiovascular mortality incidence versus placebo [29].…”
Section: Labas and Lamas In Copdmentioning
confidence: 99%
“…Tiotropium was associated with higher cardiovascular mortality risk. However, in another context, tiotropium was shown to be more effective in reducing exacerbations than salmeterol and indacaterol, regardless of association with inhaled corticosteroids [27,28]. Moreover, the UPLIFT study (Understanding Potential Long-term Impacts on Function with Tiotropium), a double-blind, randomised, placebo-controlled clinical trial conducted on >6000 patients (followed up for 4 years), revealed a reduced acute myocardial infarction and cardiovascular mortality incidence versus placebo [29].…”
Section: Labas and Lamas In Copdmentioning
confidence: 99%
“…Until recently tiotropium was the only marketed LAMA, but other LAMAs are currently available, such as aclidinium and glycopyrronium. Umeclidinium bromide (UMEC) is also a newer LAMA, being a potent antagonist of M3 muscarinic receptors with long-term duration of bronchodilation 1 . Several controlled trials have suggested that the optimal dosing of UMEC is 62.5 mg once daily (OD).…”
mentioning
confidence: 99%
“…Few head-to-head studies between LAMAs have been performed, but the current idea is that they are equivalent in efficacy. However, as more LAMAs are available, clinicians shall decide the first choice among LAMAs and possibly safety may have a key-role 1 . Even if inhaled LAMAs are generally considered to be safe, muscarinic receptors are expressed not only in the lungs, but also at the level of heart, digestive and urinary apparatus.…”
mentioning
confidence: 99%
See 2 more Smart Citations